Why HID headlights bother older drivers. Issue 1 (1st January 2003) - Mainster, M A; Timberlake, G T
Abstract : Driving requires effective coordination of visual, motor, and cognitive skills. Visual skills are pushed to their limit at night by decreased illumination and by disabling glare from oncoming headlights. High intensity discharge (HID) headlamps project light farther down roads, improving their owner's driving safety by increasing the time available for reaction to potential problems. Glare is proportional to headlamp brightness, however, so increasing headlamp brightness also increases potential glare for oncoming drivers, particularly on curving two lane roads. This problem is worse for older drivers because of their increased intraocular light scattering, glare sensitivity, and photostress recovery time. An analysis of automobile headlights, intraocular stray light, glare, and night driving shows that brightness rather than blueness is the primary reason for the visual problems that HID headlights can cause for older drivers who confront them. The increased light projected by HID headlights is potentially valuable, but serious questions remain regarding how and where it should be projected.